Influence of Job Related Factors on Encouraging Savings for Health Care towards Old Age among Nurses in a Municipality, Ghana - Kolekang, Felicia; Werekoh, Kwasi Awuah-; Afari, Augustine Adomah- (International Journal of Social and Administrative Sciences, 2019)
In Ghana, the ageing population is projected to increase from 6.7% in 2010, to 11.9% by the year 2050. Meanwhile, the National Health Insurance Scheme (NHIS), does not include most age-related diseases. This makes it necessary for workers to make savings for health care towards their old age. The study determined the influence of job-related factors on savings for health care towards old age among nurses in a municipality in the Greater Accra Region. Data was collected using quantitative methods where 227 nurses from three health facilities responded to a structured questionnaire. Data were analysed using STATA version 15.1. Basic descriptive statistics were run, and the relationship between variables was analysed using simple and multiple logistic regression. A 95% confidence level (α=0.05) was used as a level of statistical significance. The prevalence of saving for health care among nurses was 80%. Job related factors such as a number of years in service, number of years left for retirement, ranks in the nursing, savings account, and incentives were significant in influencing savings for health care towards old age (p=0.002). Policy makers and senior management of health institutions should include; incentive packages, in the form of increased salaries, improved human resources policies; introduce early comprehensive pre-retirement education for all nurses to enable them to save for health care towards old age.